Hypothalamic concentration of kisspeptin and GnRH during breeding season (BS) and non breeding season (NBS) in sheep - Urias Castro, Christian, author; Nett, Terry, advisor; Clay, Colin, advisor; Han, Hyng Chul, committee member; Bouma, Gerrit, committee member (Colorado State University. Libraries, 2016)
The kisspeptin system has emerged as an important regulator of mammalian reproduction. In ewes, kisspeptin neurons are located in specific hypothalamic regions such as the preoptic area (POA) and medio-basal hypothalamus (MBH) which include the arcuate nucleus (ARC). A specific radioimmunoassay (RIA) for the quantification of hypothalamic kisspeptin was developed to test the hypothesis that estradiol decreases the production of kisspeptin during the NBS in the MBH in addition to other forebrain areas that harbor kisspeptin neurons and/or axons such as the POA, the anterior hypothalamic area (AHA), and the median eminence (ME). The kisspeptin RIA results indicated that the concentrations of kisspeptin per milligram of tissue were decreased during NBS in the MBH and the POA with a tendency for lower kisspeptin concentrations observed in the AHA. Likewise, the total content of kisspeptin was decreased in the MBH and POA during the NBS, with a similar tendency for lower content of kisspeptin observed in the AHA during the NBS. Supporting the notion that kisspeptin modulates secretion of GnRH at the level of the ME, a positive correlation between these neuropeptides was observed during the BS in this region. It may be, that kisspeptin neurons are relevant for the seasonal regulation of GnRH and LH secretion exerted by estradiol, since the GnRH neurons do not express estrogen receptor alpha (ERα) which is the relevant ER subtype for the regulation of the hypothalamic pituitary gonadal axis (GnRH/LH pulsatility). We investigated if the negative feedback exerted by estradiol during the NBS, promoting a decrease in the concentrations of kisspeptin in the ARC, can be blocked by the intracerebral ventricular (ICV) administration of an estradiol antagonist (ICI) to promote an increase in LH pulsatility. As expected, in ewes that received the ICI treatment an increase in the average number of LH pulses was observed. The increased frequency in LH pulsatility was probably a consequence of eliminating estradiol inhibitory actions over ARC kisspeptin neurons which send axonal projections to the ME and promote the release of GnRH, and thus LH. Interestingly, the ME is a circumventricular organ (CVO) located outside of the blood brain barrier (BBB). Ovariectomized ewes were immunized against kisspeptin and antiserum to kisspeptin generated. The antibodies to kisspeptin were intended to eliminate kisspeptin release from the ME and consequently block kisspeptin input to GnRH axon terminals. The blockade of kisspeptin input to GnRH axon terminals was intended to inhibit the release of GnRH and hence LH. When compared to controls, ewes immunized against kisspeptin tended to have lower average and basal secretion of LH. The lack of significant decrease observed in immunized ewes suggests that higher titers to kisspeptin could be needed to fully suppress GnRH and hence LH pulsatility. Still, the tendency for lower levels of LH observed in immunized ewes suggest that kisspeptin release from the ME is relevant for the modulation of the pulsatile secretion of GnRH and thus LH. Likewise, delayed onset of the preovulatory like surge of LH in immunized ewes suggests a partial inhibition of the massive release of kisspeptin/GnRH was obtained during the start of the surge. However the possibility that the preovulatory surge of kisspeptin/GnRH is also regulated inside the BBB or that kisspeptin independent or indirect mechanisms play an important role in the generation of the GnRH/LH surge in ewes cannot be ruled out.
Keywords: kisspeptin; radio innuno assay; kisspeptin antibodies; estrogen receptor